The Differences in Epistemology in Islam: Traditional, Rational, And Sufistic Approaches - Putra, Bilal Indra; Husni, Husni; Wahyuni , Sri (Jurnal Indonesia Sosial Sains, 2025)
This study examines the diverse epistemological approaches in Islam - traditional (naqli), rational (aqli), and sufistic (dzauqi) - which reflect different methods of acquiring and validating knowledge. The research problem stems from the frequent isolation of these approaches in contemporary discourse, creating a gap in understanding their potential integration and collective contribution to Islamic thought. The objectives are threefold: (1) to analyze the methodological foundations of each approach, (2) to compare their strengths and limitations, and (3) to explore their complementary roles in addressing modern epistemological challenges. Using qualitative methodology with literature analysis, the study draws from classical Islamic texts and works by key figures like Al-Ghazali, Ibn Sina, and Ibn Arabi. The findings reveal that while the naqli approach emphasizes textual authority, aqli prioritizes reason, and dzauqi values spiritual experience, these methods are not mutually exclusive. Rather, they form a dynamic spectrum of knowledge acquisition in Islam. The research demonstrates how integrating these approaches can enrich contemporary Islamic scholarship, particularly in reconciling faith with modern science and addressing secular epistemological frameworks. The implications suggest the need for educational models that harmonize textual, rational, and spiritual dimensions of knowledge, offering Muslims a more holistic approach to navigating today's intellectual landscape while maintaining theological integrity.